Modernités littéraires en Afrique : injonction ou évidence ? - Xavier Garnier (Itinéraires)
The claim for literary and artistic modernity on the African continent is linked to the slogan of modernization, constantly applied, since the beginning of colonization up to the present days, in social and political areas. The technological dimension of such modernization, the split it entails between a world of tradition and a world of modernity, the forms of individualism that it generates inside societies often considered to be holist societies, all these topics could only been taken into account by a literature that, from the starting point, situated itself on the side of modernity.